God's kingdom and God's son : the background in Mark's christology from concepts of kingship in the Psalms - Rowe, Robert D. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 2002)
How is the kingdom of God related to Messianic kingship (or divine sonship)? Starting from what he terms a 'two-tier' kingship in the Psalms, Robert Rowe explores the linkage of these terms in Mark's gospel. The linked concepts - God's kingship and Davidic (Messianic) kingship - are traced from the Psalms and Isaiah 40-66, through the Dead Sea Scrolls and other inter-testamental documents, into Mark's gospel. Mark's characterization of Jesus as Messiah is shown to centre around four royal Psalms (2; 22; 110; 118). Contributing to the continuing study of the Old Testament in the New, Rowe argues that the concepts of God's kingdom and the Messiah are inherently closely related. This has importance both for the study of the historical Jesus, and for Mark's presentation of God and Jesus in his gospel.